THE IMPACT OF ENTREPRENEURIAL KNOWLEDGE, ENTREPRENEURIAL SKILLS, AND INNOVATION ON THE COMPETITIVE ABILITY OF WOMEN MANAGED SMES: A CASE STUDY OF SMES IN MEDAN CITY - Siagian, Supriadi; Reynols Manday, Choncho (Universitas Islam Lamongan, 2024)
Micro, Small and Medium Enterprises (MSMEs) are part of the independent Indonesian economy and have great potential in improving welfare. MSMEs contribute to gross domestic product (GDP) income of 60% of the 65.46 million total MSMEs in Indonesia. Knowledge, skills and innovation are one way to improve the competitiveness of MSMEs. Therefore, the purpose of this study is to analyze the role of entrepreneurial knowledge, entrepreneurial skills and innovation on the ability competitiveness of MSMEs managed by women, especially in Medan city. This study uses a quantitative approach and data collection methods in this study in the form of questionnaires that will be distributed to female MSME actors in Medan city both online and offline using Likert Scale measurements. The population in this study is MSMEs managed by women. The population size of female MSME entrepreneurs is 24,925 MSMEs. The sampling technique uses a non-probability sampling technique with sampling using purposive sampling using the Slovin formula with a total of 394 respondents. The data processing method uses SEM-PLS and uses SPSS 24 software. The results of the study show that entrepreneurial knowledge, entrepreneurial skills and innovation have an effect on the ability competitiveness of MSMEs managed by women, especially in Medan city. So in this case, the importance of the role of knowledge and innovation in improving the performance of MSMEs